Architecture as a Syntax for Elderly Rejuvenation Design Proposal for Tropical Climate Country - Grace Novita Silalahi; FX. Teddy Badai Samodra (IPTEK Journal of Proceedings Series, 2019)
In an urban environment, the growing number of elderly population increases because of the increase in life quality.  In order to face the increasing amount of elderly, the elderly needs to be empowered so they can still productive in their aging phase. This design research aims to upgrade the quality of Small Office/Home Office (SOHO) for the elderly through behavior setting of elderly by using Space Syntax. Field measurement and interview were conducted to obtain data for simulation using Depth Map analysis to predict room connection and integrity. The result highlighted that resilience design conducted through respect to the relation between the room that can lead elderly rejuvenation in tropical climate country